Coherent high-frequency vibrational dynamics in the excited electronic state of all-trans retinal derivatives - Kraack, Jan Philip; Buckup, Tiago; Motzkus, Marcus (The journal of physical chemistry letters, 2013)
Coherent vibrational dynamics of retinal in excited electronic states are of primary importance in the understanding of photobiology. Using pump-DFWM, we demonstrate for the first time the existence of coherent double-bond high-frequency modulations (>1300 cm-1) in the excited electronic state of different retinal derivatives. All-trans retinal as well as retinal Schiff bases exhibit a partial frequency downshift of the C═C double-bond mode from ∼1580 cm-1 in the ground state to 1510 cm-1 in the excited state. In addition, a new vibrational band at ∼1700 cm-1 assigned to the C═N stretching mode in retinal Schiff bases in the excited state is detected. The newly reported bands are observed only in specific spectral regions of excited-state absorption. Implications regarding the observation of vibrational coherences in naturally occurring retinal protonated Schiff bases in rhodopsins are discussed.